Assessment of Peri-implant Bone Disorders Treatment by Bone Replacements: Histological and Immunhistochemical Analysis in the Rabbit Tibia - Asmaa Ali (Journal of Global Pharma Technology, 2018)
Aims: to assess the efficiency of bone replacements in peri-implant disorders formed in the rabbit tibia. Methods: Twenty-four rabbits used to receive 36 screws of implant in their tibia. A circular bone defect 6.1 mm in diameter/4 millimeter depth made in the rabbit tibia. Dental implant sgrew "4.1 mm × 8.5 mm" placed beyond formation of defect, offering a "2-mm space". These spaces were lauded either with blood clot (BC), particulate Bio-Oss(R) (PBO), or Bio-Oss(R) Collagen (BOC). Eight animals were euthanized after 30, 45, and 60 days. Histological and immunehistochemical analyses for protein expression of osteocalcin (OC), OPG, and RANKL, were estimated. Results: At 45 and 60 days, between the PBO and BOC categories and also in the PBO and BC categories, RANKL expression was significantly different. At 8weeks, there was higher significant relation of OPG expression in the PBO category than BC category. Conclusions: An indication of our data as compared to BC and PBO, BOC give good bone healing that was described by high OC, and OPG immunolabeling. So with PBO, BOC give hopeful biological characteristics supporting its plausible application in peri-implant spaces osteoconductive grafts filling.Keywords: Osseo integration, Bone replacements, Implant, RANKL, Osteocalcin.